2015
DOI: 10.1098/rsob.150118
|View full text |Cite
|
Sign up to set email alerts
|

The human parasite Leishmania amazonensis downregulates iNOS expression via NF-κB p50/p50 homodimer: role of the PI3K/Akt pathway

Abstract: Leishmania amazonensis activates the NF-κB transcriptional repressor homodimer (p50/p50) and promotes nitric oxide synthase (iNOS) downregulation. We investigated the role of PI3K/Akt in p50/p50 NF-κB activation and the effect on iNOS expression in L. amazonensis infection. The increased occupancy of p50/p50 on the iNOS promoter of infected macrophages was observed and we demonstrated that both p50/p50 NF-κB induction and iNOS downregulation in infected macrophages depended on PI3K/Akt activation. Importantly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In contrast, induction of Akt1 shRNA with doxycycline resulted in a 40% reduction in the number of infected cells ( Figure 4c). This result was in agreement with the results of Calegari-Silva et al (2015) who showed that in THP-1 human cells transfected with Akt1 shRNA, the survival of Leishmania parasites was significantly reduced. We then proceeded to assess the efficacy of miltefosine in these cells with doxycycline co-incubation.…”
Section: Miltefosine Is Less Effective Against Leishmania After Aktsupporting
confidence: 93%
“…In contrast, induction of Akt1 shRNA with doxycycline resulted in a 40% reduction in the number of infected cells ( Figure 4c). This result was in agreement with the results of Calegari-Silva et al (2015) who showed that in THP-1 human cells transfected with Akt1 shRNA, the survival of Leishmania parasites was significantly reduced. We then proceeded to assess the efficacy of miltefosine in these cells with doxycycline co-incubation.…”
Section: Miltefosine Is Less Effective Against Leishmania After Aktsupporting
confidence: 93%
“…In this regard, it is noteworthy that L. amazonensis infection in macrophages activates the p50/p50 homodimer, a NF-κB transcriptional repressor. Inhibition of NF-κB-dependent gene transcription by p50/p50 homodimer has been attributed to cause downregulation of iNOS expression in L. amazonensis infection (43, 44). It is therefore tempting to speculate that RIPK1 may promote canonical NF-κB activation to counteract this inhibitory signal from p50/p50.…”
Section: Discussionmentioning
confidence: 99%
“…In their study Calegari-Silva et al (2015) (14) observed a reduction in infection in cells in which PKB/AKT levels were suppressed by siRNA treatment. This suggests that Leishmania survival in macrophages, even in the absence of any additional activation stimulus is dependent on activation of PKB/AKT.…”
Section: Outstanding Unresolved Observationsmentioning
confidence: 97%
“…As stated earlier, Lambertz et al (2012) (6) presented a comprehensive review of studies that demonstrated the critical of PKB/Akt signaling in Leishmania infections. More recent studies include a report by Calegari-Silva et al (2015) (14) who evaluated the role of PKB/Akt in the inhibition of nitric oxide release in L. amazonensis infections. Specifically, they considered the role of PKB/Akt in the activation of NFκB, which has been shown to control the transcription of the iNOS gene.…”
Section: Pi3k Signaling In Leishmania Infectionsmentioning
confidence: 99%